Peningkatan Kompetensi Komunikasi Bahasa Inggris Pramuwisata Lokal Desa Tista Melalui Pelatihan Merancang Tour Itinerary - Ni Nyoman Deni Ariyaningsih; I Putu Andri Permana; Ida Ayu Putri Gita Ardiantari; Putu Regina Yowana Pratiwi (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The importance of a tour guide competence and professionalism is the rational of this community service program.The focus of this program is to increase the competence of local tour guides in English by being able to design tour itinerary. This activity was done in Tista Village that is located in Kerambitan District, Tabanan Regency, Bali. The purpose of the activity is to help tourism actors especially local tour guides in Tista Village to enhance their English as one of the competency demands. Community Based Research (CBR) approach was implemented that prioritizes community needs and allows space for local wisdom as knowledge and solutions for the community. The service program was carried out using several methods, namely the lecturing method, question and answer method as well as discussion, as well as demonstration and simulation methods. Providing added value for local tour guides, the activities also include designing tour packages and practicing explaining them in English. The application of role play activities creates a more active and attractive learning atmosphere and has succeeded in increasing the participants' self-confidence as local tour guides. Through training activities in the community service program, the participants are able to understand and practice the English language used in explaining tour itinerary and packages.